Hubungan Kunjungan Antenatal Care (ANC) dengan Kejadian Bayi Berat Lahir Rendah di Kecamatan Babakan Madang, Kabupaten Bogor - Fitratur Rahmah Agustina; Trini Sudiarti; Samnil Astuti Fitri; Riska Rusydi (Lembaga Pengembangan Kinerja Dosen, 2025)
Children with low birth weight have a higher risk of death in the first month of life, experience growth disorders, developmental delays, lower IQ levels, and increase the risk of developing degenerative diseases in old age. This study aims to determine the relationship between ANC visit and the incidence of LBW in Babakan Madang District, Bogor Regency in 2019. The research design used was cross-sectional. This study used secondary data obtained from the PITTA B umbrella research in 2019. The results showed that 5.8% of children experienced LBW in Babakan Madang District in 2019. The proportion of LBW incidence was greater in mothers who did not had an ANC visit (11.6%) compared to mothers who had an ANC visit. (5.6%). The results of the chi-square analysis showed that there was no significant relationship between ANC visit and the incidence of LBW (p = 0.277). The researcher suggested that the Bogor Regency Health Office be able to improve LBW prevention interventions, such as improving the quality of antenatal care, and educating pregnant women about the importance of antenatal care.